PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PERUSAHAAN SEKTOR TELEKOMUNIKASI YANG TERDAPAT DI BURSA EFEK INDONESIA PERIODE 2014-2020 - Suryani Suryani (Nusantara Hasana Berdikari, 2022)
This study aims to analyze the effect of Current Ratio, Debt to Equity Ratio, Total Assets Turnover and Net Profit Margin on changes in a company's profit. The population used in this study are 6 telecommunications sector companies listed on the Indonesia Stock Exchange (IDX) in the 2014-2020 period. By using purposive sampling method, the samples in this study were 5 (five) companies. The data were analyzed using multiple linear regression using SPSS version 23. The results showed that the current ratio variable had a positive and significant effect on profit changes, the debt to equity ratio and turn assets turnover variables had a negative effect on profit changes, and the net profit margin variable did not effect on changes in profit.